The Function of Sound in the Gothic Novels of Ann Radcliffe, Matthew Lewis and Charles Maturin - Angela M. Archambault (Etudes Epistémè, 2016)
In the decades that followed Horace Walpole’s pioneer novel of the new Gothic genre, Gothic literature would prove unruly in its evolution and would veer towards a markedly audible experience in the works of Radcliffe, Lewis and Maturin during the last decade of the eighteenth century. While these novelists honored Walpole’s thematic requisites of murder, transgression and abundant architectural entrapments (castles, abbeys, and cloisters) – these authors supplemented the visual experience with a fresh, previously unexplored ingredient: sound. What seems to emerge from these texts is a sort of Gothic soundtrack whose noise, music and voice is capable of triggering panic and ushering in greater unpredictability. While Gothicism had already existed as literary genre well beyond the firm grasp of logic and control of human law and reason, sound begins to emerge, and functions as a textual device that amplifies these notions of terror. Sound, much like the immortal bodies of evil Gothic protagonists who pass through walls and topple morality, is unable to be managed or contained. Sound wafts over walls, passes through latched doors and knows no real barrier. Specifically, Gothic novelists Radcliffe, Lewis and Maturin experiment with the potential of sound a menacing device by orchestrating cacophony, gloomy chants and disembodied voices. Unable to be governed, it is, therefore in its very essence, an additional, albeit elusive, element that fuels the genre.